Nutritional value and bioaccumulation of heavy metals in muscle tissues of five commercially important marine fish species from the Red Sea - Younis, Elsayed M. (Saudi J Biol Sci, 2021)
The study evaluated the nutritional quality and investigated the heavy metals concentration in muscle tissues of five commercially important marine fish species, including brownspotted grouper (Epinephelus chlorostigma), squaretail coralgrouper (Plectropomus areolatus), black pomfret (Parastromateus niger), goldbanded jobfish (Pristipomoides multidens), and blueskin seabream (Polysteganus coeruleopunctatus) from the Red Sea, Jeddah Coast, Saudi Arabia. Significant differences (p < 0.05) were observed in the proximate chemical composition of fish muscles in these species. The highest protein content (17.66 ± 0.58%) was achieved in blueskin seabream while the lowest (15.28 ± 0.46%) was observed in brownspotted grouper. The highest lipid content (2.97 ± 0.45%) was recorded in squaretail coralgrouper while the lowest (1.52 ± 0.26%) was observed in blueskin seabream. Heavy metal concentrations varied significantly within and between fish species under study (p < 0.05). Significant differences in the concentration of heavy metals among fish species were recorded. Results revealed that the bioaccumulation of Cr, Fe, Ni, and Cd in muscles of fish species under study was higher than the standard concentration, but that of Mn, Cu, and Pb were less than the standard concentration recommended in the EU, FAO, and WHO guidelines. In conclusion, these fish species represent a high-quality food source but is unsafe due to the level of certain minerals in their tissues. Results also indicated that the Red Sea environment is contaminated with heavy metals, which was reflected in the tissues of fishes used in this study.